A review of the behaviour and design of steel–concrete composite shear walls. (June 2021) - Mo, Jun; Uy, Brian; Li, Dongxu; Thai, Huu-Tai; Tran, Hau
Abstract: Concrete filled composite shear wall (CFCSW) can provide many benefits by taking advantages of two components. This paper reviews the development of CFCSW in terms of connection configurations and steel plate types. The structural behaviour of CFCSW under various loading conditions is summarised and discussed. The effects of many parameters, including axial load ratio, steel plate reinforcement ratio and spacing of connectors on the performance of CFCSW are reviewed. The equations in current standards are performed and compared. The results indicate that the increase of axial force ratio leads to rapid stiffness degradation and strength degradation of CFCSW when subjected to cyclic lateral loading. Higher steel plate reinforcement ratio can contribute to higher ductility and axial resistance, however composite action is dramatically reduced. Spacing of shear connectors has a great influence on the slenderness of CFCSW. Large connector spacing leads to local buckling of steel plates in the elastic range which should be avoided. CFST boundary elements can enhance the structural performance of CFCSW which has been widely adopted in recent researches and projects.